Optimasi Penjadwalan Kegiatan Belajar Mengajar Pada Pondok Pesantren Menggunakan Algoritme Genetika (Studi Kasus : Pondok Pesantren Yayasan Bani Syihab Nasrulloh) - Yamlikho Karma; Nurul Hidayat; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The manual scheduling process is considered inefficient because it takes a long time. If the number of components increases or the amount of data per component increases, scheduling problems will be more complex.. The expected result of the schedule is not only a schedule that does not clash with teacher meeting, but a schedule that can be adjusted according to several conditions that must be fulfilled in the schedule. A genetic algorithm is an iterative, adaptive and probabilistic algorithm for global optimization.. The chromosome initialization process is generated from the teacher's assignment data with an integer number representation, where each gene contains a randomly generated assignment code. Each chromosome with the highest fitness value represents the solution of the course schedule. From the testing process, it was found that the best population number is 100, the combined numbers of Cr and Mr are 0,5 and 0,5, and the generation number is 1000. These parameters are used for the process of finding a solution so that the fitness number is 0,9985.